2016
DOI: 10.1590/2317-4889201620160012
|View full text |Cite
|
Sign up to set email alerts
|

Age, provenance and tectonic setting of the high-grade Jequitinhonha Complex, Araçuaí Orogen, eastern Brazil

Abstract: ABSTRACT:The Jequitinhonha Complex of the northeastern Araçuaí orogen is an extensive sedimentary unit metamorphosed in the amphibolite-granulite facies transition around 580-545 Ma. The unit consists of Al-rich (kinzigitic) paragneisses with decametric intercalations of graphite gneisses and quartzites, and centimetric to metric lenses of calcsilicate rocks. A new detrital zircon U-Pb age spectrum is reported for a sample of quartzite, and whole-rock geochemical (major and trace elements, 9 samples) and Sm-Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This has been documented by a variety of geothermometers applied to stable mineral parageneses in granulites and migmatites of the orogen, as discussed in detail by Moraes et al (), who found temperature values around 850°C in the northern part of the hot internal domain. This is consistent with other results, which generally show peak metamorphic temperatures in excess of 750°C for this domain, as illustrated in Figure c (Belém, ; Dias et al, ; Gradim et al, ; Gonçalves et al, ; Moraes et al, ; Munhá et al, ; Uhlein et al, ). A rather well‐studied portion of this internal hot part of the orogen is the Carlos Chagas anatectic domain (CC in Figure ), where vast amounts of crustal melt have been produced and deformed in the nonsolid state at midcrustal levels during the orogeny (Cavalcante et al, , ).…”
Section: The Araçuaí‐west Congo Orogensupporting
confidence: 93%
See 1 more Smart Citation
“…This has been documented by a variety of geothermometers applied to stable mineral parageneses in granulites and migmatites of the orogen, as discussed in detail by Moraes et al (), who found temperature values around 850°C in the northern part of the hot internal domain. This is consistent with other results, which generally show peak metamorphic temperatures in excess of 750°C for this domain, as illustrated in Figure c (Belém, ; Dias et al, ; Gradim et al, ; Gonçalves et al, ; Moraes et al, ; Munhá et al, ; Uhlein et al, ). A rather well‐studied portion of this internal hot part of the orogen is the Carlos Chagas anatectic domain (CC in Figure ), where vast amounts of crustal melt have been produced and deformed in the nonsolid state at midcrustal levels during the orogeny (Cavalcante et al, , ).…”
Section: The Araçuaí‐west Congo Orogensupporting
confidence: 93%
“…Several estimates of paleopressures associated with the metamorphic peak in the internal part of the orogen have been presented in the literature, generally varying between 0.5 and 0.7 GPa. (Belém, ; Dias et al, ; Gradim et al, ; Gonçalves et al, ; Moraes et al, ; Munhá et al, ; Petitgirard et al, ; Uhlein et al, ). The highest pressure (0.8 GPa) for the main Araçuaí‐West Congo orogeny was found in the southernmost part of the Araçuaí belt (Bento dos Santos et al, ).…”
Section: The Araçuaí‐west Congo Orogenmentioning
confidence: 99%
“…Paragneisses showing evidence of partial melting are widespread in the internal domain (blue unit 3 in Fig. 3), and are at least in part considered to represent partially molten Macaúbas Group (e.g., Dias et al, 2016), but also synorogenic metasediments (Nova Venécia Group; Richter et al, 2016).…”
Section: The Internal Domain (Hinterland)mentioning
confidence: 99%
“…8). Compared to the Vazante and Canastra groups, Gonçalves- Dias et al (2016) interpreted the provenance patterns of the Jequitinhonha Complex, located on the SE border of the SFC, in the Araçuaí Orogen, as resulted from the mixture between cratonic and Tonian rift-related volcanic rocks of the West Congo belt (Tack et al 2001). Caxito et al (2014a) reached the same conclusion for the Canabravinha Formation, in the Rio Preto Fold Belt, northwestern margin of the SFC.…”
Section: Discussionmentioning
confidence: 99%